Penghulu’s Contribution to the Strengthening of Religious Moderation in Nunukan Regency - Syahrul Afandi (Mazahibuna: Jurnal Perbandingan Mazhab, 2022)
The aim of this study is to investigate the role of the prince in promoting religious moderation in Nunukan Regency. It is also focus on examining the implementation of religious moderation in the performance of the prince's duties, as measured by the religious moderation indicators of the Ministry of Religion, namely national commitment, tolerance, anti-violence, and accommodation of local culture. This qualitative investigation was conducted at the office space of the Ministry of Religion, Nunukan Regency. Following this, the acquired data in this study were examined in accordance with the theory of Miles and Huberman, including data reduction, data presentation, and conclusion drafting. The results show that the presence of the penghulu in the community as the executor of public services in the kepenghuluan sector and as a religious figure gave the penghulu a strategic role and position in promoting religious moderation in Nunukan Regency. The role of the Penghulu in bolstering religious moderation through the implementation of tasks, such as marriage or reconciliation services and guidance, as well as the development of leadership and guidance for the Islamic community and their religious character, contributes to the maintenance of a safe and hospitable environment in Nunukan Regency, thereby preserving its pluralism. Furthermore, the chieftains in this Regency have generally implemented the four indicators of religious moderation established by the Ministry of Religion through the execution of their duties, activities, and pastoral programs. The role of the penghulu in promoting religious moderation in Nunukan Regency was examined in this study since the description of the penghulu's activities pertaining to handling and assisting the potential for socio-religious conflict has not been thoroughly explored.